Perception of micro entrepreneurs towards Qardh al Hasan loan at MARA Pasir Puteh / Nurbahiah Mohamed Metar@Mukhtar - Mohamed Metar@Mukhtar, Nurbahiah (Academy of Contemporary Islamic Studies, 2018)
In Malaysia, people are paying more attention to the so called Islamic economy. This is seen to arise from their increasing need to the establishment of financial institutions that are based in Shariah (Islamic law) and regardless whether or not the institution uses a banking system such as Majlis Amanah Rakyat (MARA). Moreover, as the majority of Malaysians are Malay and Muslim, the opportunity for a financial market that is based on Shariah is far reaching. At MARA, they had provided Islamic loan like Murabahah, Bai Bithaman Ajil, Bai Inah and Also Qardh Al Hasan. One of the Islamic microfinance that the researcher wants to highlight here is Qardh Al Hasan. This loan is not very famous among Malaysians and most of them did not know at all the existence of this kind of loan. So this study will analyze the perception of micro entrepreneur towards Qardh al Hasan loan at MARA Pasir Puteh. The process of this research included library research and field research. The library research was conducted to obtain information from books, pamphlet, papers, journals, newspapers and the data associated with reference and research topic, while the field research used questionnaires. This study involves 65 respondents out of 84 borrowers at MARA Pasir Puteh. The data collected through the questionnaires were analyzed using Statistical Product and Service Solutions (SPSS) software 20.0.